The higher education management in medical universities during the COVID-19 pandemic - Lak , Saeed; Ghourchian, Nadergholi; Jamali , Akhtar (Social Determinants of Health, 2022)
Background: The use of electronic technology plays a key role in the change in higher education management. This study aimed to assess the necessity of adaptation of electronic learning systems management during the COVID-19 pandemic. Methods: The present study was mixed research. Its statistical population in the qualitative section included 50 experts in higher education management of medical universities. The statistical population in the quantitative section included 242 department heads of 65 medical universities selected according to Morgan’s table. Purposeful sampling was used in the qualitative section and cluster random in the quantitative section. The interview was used in the qualitative section and a researcher-made questionnaire was used in the quantitative section. Qualitative data analysis was performed with MAXQDA 2019 software and quantitative data analysis was performed with SPSS software. Results: In the qualitative section, 9 general categories were obtained. In the quantitative section, the results of the one-sample t-test in the dimensions of development of technology and electronic service, expansion of virtual and integrated education, enhancing the quality of learning, expanding research, access to scientific resources, the efficiency of the educational system and optimization of capital and financial affairs of the current status of higher education management in medical universities were determined. Conclusion: For the development of e-learning at the university level during the COVID-19 pandemic, it is necessary to know the motivating factors and barriers well and use the gained experience to select appropriate strategies to accelerate the development process of e-learning.